A SIMBIOSE DISCURSIVA ENTRE RELIGIÃO E MERCADO: Um estudo do discurso da Igreja Universal do Reino de Deus na perspectiva do consumo - SOUZA, RONIVALDO MOREIRA DE (2017)
This research investigated the relationship between religion and the crystallized market in the discourse of the Universal Church of the Kingdom of God. Understanding the space of exchanges between buyers - which we call the market - is sustained by an avid consumption of goods and services, we anchor our perceptions in consumer theories in the contemporary world. Next, by the lenses of the Sciences of Religions, we investigate the bases of what is denominated religion and its adequacy to the logic of the consumer society. To investigate the discursive correspondence in which the meanings emerge, the research adopts the theoretical-methodological concepts of Discourse Analysis of the French School. The main objective of this study is to analyze the functioning and the process of production of meanings in the imbrication of two discursive fields - the religious and the market - finding in the regularities and differences the constitutive elements of the discourse of the Universal Church of the Kingdom of God. The corpus of the research is composed by testimonies of the faithful and the messages of the shepherds that the Church offers on their Youtube channel: IURD TV; and on its website: universal.org. The thesis that guides the discussions in this work is that religion and market establish a symbiotic relationship in which consumption appropriates the sacred and the sacred appropriates consumption. We adopt the biological metaphor of symbiosis to understand the life in common between these two institutions - religion and market - which, despite their different nature, cooperate with each other in the art of coexistence. We find that the discourse of the Universal Church builds a symbiosis between the market and the religious, making possible a sacralization of consumption and a marketization of the sacred.